An electric vehicle model and validation using a Nissan Leaf: A Python-based object-oriented programming approach. (July 2018) - Howroyd, Simon; Thring, Rob
Electric vehicles are becoming more and more prevalent, especially with major manufacturers announcing that they will be focusing on electric or hybrid vehicles in the future. This article describes an object-oriented approach to a vehicle model using Python 3. This approach allows for flexibility of vehicle design. The key parameters were input to define the specific vehicle for validation, in this case a Nissan Leaf. It is anticipated that this flexibility will lead to rapid exploratory design of vehicle variants, such as four-wheel drive, independent wheel drive and multiple electrical sources. The model had its objects individually validated before the whole vehicle was verified against common drive cycles and a real-world drive in the United Kingdom recorded using an On-board Diagnostics (OBD2) Bluetooth dongle.